Law No. 61 of the year 2010 On Adding A New Article Under No. 42 (Bis) To The Law On Protection Of Antiquities Promulgated By Law No. 117 Of The Year 1983 = قانون رقم 61 لسنة 2010 بإضافة مادة جديدة برقم 42 مكرراً إلى قانون حماية الآثار الصادر بالقانون رقم 117 لسنة 1983 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.